Lymph node evaluation for treatment of adenocarcinoma of the pancreas. (September 2015) - Marmor, Schelomo; Burke, Erin E.; Portschy, Pamela R.; Virnig, Beth A.; Jensen, Eric H.; Tuttle, Todd M.
Abstract Background Increased lymph node evaluation has been associated with improved survival rates in patients with pancreatic cancer. We sought to evaluate the trends and factors associated with lymph node examination over time and the effects on survival. Methods Using the Surveillance, Epidemiology and End Results database, we conducted an analysis of adults with adenocarcinoma of the pancreas who underwent surgical resection. Using the Cochrane Armitage test for trend and logistic regression we identified factors associated with lymph node evaluation. Kaplan–Meier and Cox proportional hazards modeling were used to examine survival. Results We identified 4831 patients who underwent surgical resection from 1990 to 2010. The proportion of patients with 15 or more lymph nodes evaluated increased from 16% to 42% (p < 0.05) and the median number of lymph nodes examined increased from 7 to 15 nodes (p < 0.05) during the study period. Overall, 56% of patients had lymph node metastases; this proportion significantly increased during the study period. Factors that were independently associated with less than 15 lymph nodes evaluated included male gender, receipt of pre-operative radiation therapy, early year of diagnosis, older age, and missing information on tumor grade and size (p < 0.05). Survival rates significantly improved when 15 or more lymph nodes were examined. Conclusion We observed a significant increase in the number of lymph nodes evaluated with pancreas cancer resection over time. Lymph node evaluation was significantly associated with patient, tumor, and treatment characteristics. Our results suggest that adequate lymph node evaluation is associated with improved survival.